Poria cocos: traditional uses, triterpenoid components and their renoprotective pharmacology - Guo Zhi-yuan; Wu Xin; Zhang Shui-juan; Yang Jian-hua; Miao Hua; Zhao Ying-yong (Acta Pharmacologica Sinica, 2025)
Poria cocos and its surface layer of Poria cocos (Schw.) Wolf (Polyporaceae), are used in traditional Chinese medicine for its diuretic and renoprotective effects. Phytochemical studies have shown that lanostane and 3,4-seco-lanostane tetracyclic triterpenoids are the main components of P. cocos and its surface layer. Accumulating evidence shows that triterpenoid components in P. cocos and its surface layer contribute to their renoprotective effect. The surface layer of P. cocos showed a stronger diuretic effect than P. cocos. The ethanol extract of the surface layer and its components improved acute kidney injury, acute kidney injury-to-chronic kidney disease transition and chronic kidney disease such as diabetic kidney disease, nephrotic syndrome and tubulointerstitial nephropathy, and protected against renal fibrosis. It has been elucidated that P. cocos and its surface layer exert a diuretic effect and improve kidney diseases through a variety of molecular mechanisms such as aberrant pathways TGF-β1/Smad, Wnt/β-catenin, IκB/NF-κB and Keap1/Nrf2 signaling as well as the activation of renin-angiotensin system, matrix metalloproteinases, aryl hydrocarbon receptor and endogenous metabolites. These studies further confirm the renoprotective effect of P. cocos and its surface layer and provide a beneficial basis to its clinical use in traditional medicine.